Bovine β-lactoglobulin-induced passive systemic anaphylaxis model using humanized NOG hIL-3/hGM-CSF transgenic mice. (7th October 2020) - Ito, Ryoji; Katano, Ikumi; Otsuka, Iyo; Takahashi, Takeshi; Suemizu, Hiroshi; Ito, Mamoru; Simons, Peter J
Abstract : A new model of anaphylaxis in humanized mice Abstract: Food allergy is a common disease caused by intake of allergen-containing foods, such as milk, eggs, peanuts and wheat. Systemic anaphylaxis is a severe hypersensitive allergic reaction resulting from degranulation of mast cells or basophils after cross-linking of surface high-affinity IgE receptors (Fcε-RI) with allergen-specific IgE and allergens. In this study, we developed a novel human mast cell/basophil-engrafted mouse model that recapitulates systemic anaphylaxis triggered by β-lactoglobulin (BLG), a major allergen found in cow's milk. Human CD34 + hematopoietic stem cells were transferred into NOG (non-Tg) or NOG hIL-3/hGM-CSF transgenic (Tg) mice. After 14–16 weeks, bovine BLG-specific human IgE was intravenously injected into humanized mice, followed by intravenous or oral bovine BLG exposure 1 day later. Body temperature in Tg, but not in non-Tg, mice gradually decreased within 10 min, and 80% of Tg mice died within 1 h by intravenous BLG exposure. Serum histamine levels and anaphylaxis scores in Tg mice were markedly increased compared to non-Tg mice. Furthermore, these allergic symptoms were significantly inhibited by epinephrine treatment of the Tg mice. Therefore, the current NOG hIL-3/hGM-CSF Tg mouse model may be useful for development of novel anaphylaxis drugs for treatment of food allergies and for safety assessment of low-allergenicity extensively hydrolyzed cow's milk whey protein-based infant formulas.